Gender-based Stereotypical Practices in Selected Industries in Metro Cebu - Louiechi Von R. Mendoza (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study made use of qualitative design as a method for describing the practices of selected industries in Metro Cebu and how gender relates to actual performance and productivity in the workplace. The researcher utilized narratives as qualitative data gathered through interviews. Interviews were made with persons who have direct influence on the hiring, promotion, dismissal, and termination (personnel management) of employees, such as the Human Resource Managers or the Company Owners. There were a total of ten (10) key informants for the study. It was found out that gender-based stereotypes, practices, and beliefs are evident in the selected industries in Metro Cebu. Hiring men is best to protect the interests of the respective companies, citing practicality and productivity considerations.